Identificación De Los Servicios Habilitados Y Normativos De La Contratación En Nueva Eps Mediante Un Dashboard (2024)
Nueva EPS, as a Health Promotion Entity, currently presents insufficiency in the identification of current contracted services according to the data collection processes that are presented in the potential areas of contracting services, therefore this project focuses on the development of a Dashboard, which is conceived as a visual and interactive interface designed so that users can access and analyze the data stored in the Data Warehouse created by applying good data governance practices. This Data Warehouse has been established as a centralized platform that integrates data from various internal sources, with the purpose of facilitating the identification of enabled services and ensuring compliance with regulations in the Nueva EPS health services contracting process.